Altered fluvial patterns in North China indicate rapid climate change linked to the Permian-Triassic mass extinction - Zhu, Zhicai (Sci Rep, 2019)
The causes of the severest crisis in the history of life around the Permian-Triassic boundary (PTB) remain controversial. Here we report that the latest Permian alluvial plains in Shanxi, North China, went through a rapid transition from meandering rivers to braided rivers and aeolian systems. Soil carbonate carbon isotope (δ(13)C), oxygen isotope (δ(18)O), and geochemical signatures of weathering intensity reveal a consistent pattern of deteriorating environments (cool, arid, and anoxic conditions) and climate fluctuations across the PTB. The synchronous ecological collapse is confirmed by a dramatic reduction or disappearance of dominant plants, tetrapods and invertebrates and a bloom of microbially-induced sedimentary structures. A similar rapid switch in fluvial style is seen worldwide (e.g. Karoo Basin, Russia, Australia) in terrestrial boundary sequences, all of which may be considered against a background of global marine regression. The synchronous global expansion of alluvial fans and high-energy braided streams is a response to abrupt climate change associated with aridity, hypoxia, acid rain, and mass wasting. Where neighbouring uplands were not uplifting or basins subsiding, alluvial fans are absent, but in these areas the climate change is evidenced by the disruption of pedogenesis.